THE U.S. NATIONAL INTEREST REDEFINITION AND THE FUTURE OF ITS LEADERSHIP IN CRITICAL REGIONS. STRONG AND SUSTAINABLE AMERICAN LEADERSHIP? - Iñigo ARBIOL OÑATE (Challenges of the Knowledge Society)
In the last half of the 20th century, the United States provided a strong centripetal leadership that brought the country to form an economy that remains the bedrock of the global financial system. America’s military superiority remains unrivaled. While far from perfect, the U.S. has the oldest democratic constitutional regime, as well as strong institutions and rule of law to accompany it, as Americans continue to enjoy an unmatched quality of life. In general the U.S. enjoys still a privileged position in the world today. For the last one hundred years, American foreign policy has rested on a commitment to use its power. Nevertheless, many criticize that over the last two decades, the U.S. has scaled down its presence, ambitions and promises in the world. Is the U.S. abnegating its leadership? Are U.S. national interests changing and refocusing towards home affairs? Or will the 21st century, due to fragile alternative powers (EU, China, Russia, …) be again an American century?